1997
DOI: 10.2188/jea.7.226
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Differences in Cord-Blood Cholesterol and Fatty-Acid Levels Among Japanese Fetuses

Abstract: Japanese FetusesTetsuo Andoh1, Hidenori Uda1,2, Nobuyuki Yoshimitsu3, Hiromichi Hatano4 , Teppei Ueda5, Youichi Iwamatsu1'2 and Suminori Akiba1We examined serum cholesterol and fatty-acid levels of cord blood and maternal blood samples collected from 193 Japanese fetuses and their mothers. Our study, which is the largest study of this kind ever conducted in Japan, is the first Japanese study reporting that total, high density lipoprotein (HDL) and non-HDL cholesterol levels in females were statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…In some studies, total cholesterol, HDL-C, LDL-C and triglycerides have been higher in female than in male neonates. 12,13 In our study, all biochemical factors examined were higher in girls than in boys, but this difference was significant only for total cholesterol and HDL-C. Although a gender difference is suggested for LDL-C and non-HDL-C components, we did not find previous studies that suggested a gender difference for combined HDL-C and non-HDL-C components in cord blood lipids.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In some studies, total cholesterol, HDL-C, LDL-C and triglycerides have been higher in female than in male neonates. 12,13 In our study, all biochemical factors examined were higher in girls than in boys, but this difference was significant only for total cholesterol and HDL-C. Although a gender difference is suggested for LDL-C and non-HDL-C components, we did not find previous studies that suggested a gender difference for combined HDL-C and non-HDL-C components in cord blood lipids.…”
Section: Discussioncontrasting
confidence: 95%
“…The gender differences in cord lipids are controversial. In some studies, total cholesterol, HDL‐C, LDL‐C and triglycerides have been higher in female than in male neonates 12,13 . In our study, all biochemical factors examined were higher in girls than in boys, but this difference was significant only for total cholesterol and HDL‐C.…”
Section: Discussioncontrasting
confidence: 60%
“…There are several studies which demonstrated these differences are already apparent at birth (22,31). These studies showed that TC, HDL-C, LDL-C and TG levels have been higher in female versus male neonates (43). Our findings also revealed that the mean of TC and LDL-C in females were significantly more than male neonates.…”
Section: Discussionsupporting
confidence: 66%
“…The serum (200 mL) or HDL supernatant (200 mL serum) was mixed with stigmasterol (400 mg) and heptadecanoic acid (200 mg) and then hydrolysed and transmethylated with 3% HCL‐methanol at 80°C for two hours. After the lipid fraction was separated by thin layer chromatography, the sterol and methylesterified fatty‐acid fractions were analysed by gas liquid chromatography 3 . The peaks were identified by relative retention time with internal standards (stigmasterol for cholesterol and heptadecanoic acid for fatty acids), then quantified using an integrator.…”
Section: Methodsmentioning
confidence: 99%